Detection of Dental and Oral Diseases Using the Oral Hygiene Index-Simplefied (OHI-S) to Enhance Public Health - Febria Nyka Dwi; Femilian Afryla; Arinawati Dian Yosi; Ranum Sari Multia; Azizah Nurul (BIO Web of Conferences)
The dental community widely recognizes that the buildup of dental plaque on teeth can lead to gingivitis, which may advance to chronic periodontitis in some instances. It is imperative to address plaque accumulation early through early detection and prevention of dental and oral issues. Regrettably, routine dental check-ups and good dental hygiene are frequently neglected by the general populace. The main purpose of the examination is to increase public awareness of the importance of dental health, provide the knowledge and skills necessary to maintain dental health, and facilitate access to high-quality dental care. Dental and oral hygiene examination was conducted on 18 people using the OHI-S (Oral Hygiene Index-Simplified) method, which revealed that a large number of them had OHI-S scores in the moderate range, indicating the need for the community to prioritize the promotion, prevention, and rehabilitation of dental health. The follow-up actions taken were to provide dental health education and referrals for dental care.